Olfactory Evaluation in Clinical Medical Practice - Červený, Květoslav; Janoušková, Karla; Vaněčková, Kristýna; Zavázalová, Šárka; Funda, David; Astl, Jaromír; Holy, Richard (Journal of clinical medicine, 2022)
The subjective and demanding nature of olfactory testing means that it is often neglected in clinic despite loss of smell leading to significant limitations in everyday life. The list of diseases associated with loss of olfaction far exceeds the field of otorhinolaryngology and can also be seen in neurodegenerative disorders. Knowledge of possible clinical testing is essential to determine a proper differential diagnosis for the loss of olfactory sense. Causes of olfactory impairment can be divided into either failure in transferring odour to the organ of perception or damage to the olfactory pathway structure itself. Examination should therefore include methods evaluating cross-sectional area and patency of the nasal cavity as well as subjective or objective assessment of olfactory function. In this report we summarize several articles, studies, and our own experiences to provide a comprehensive review of their current clinical usage including their benefits, limitations, and possible outcomes. We also discuss the mechanism of olfaction step by step to provide a full understanding of the possible errors depending on the localization in the pathway and the methods designed for their detection. We discuss the correlation of the microbiome in nasal polyposis and chronic rhinitis with olfactory impairment using objective olfactometry. The topic of objective olfactometry and the examination of olfactory event-related potentials (OERP) is commented upon in detail.
Keywords: hyposmia; objective olfactometry; olfactory event-related potentials; olfactory system; parosmia; anosmia; odourants